Using SEO to leverage digital visibility and atract visitors: the case of termas de Chaves - Mendonça, Vítor (2022)
Digital presence, especially using websites, is currently one of the pillars for effective communication in the field of marketing. However, it appears that many organizations, despite making high investments in development, even if they present a visually attractive website, face difficulties in attracting visitors. In the case of the tourism sector, in which competition takes place on a global level, it is even more pressing for technologies to reach potential stakeholders, first attracting visitors, then seducing them and converting them into customers. In this context, digital marketing techniques, and more specifically, website optimization techniques to improve their visibility by search engines (Search Engine Optimization) are the key to leveraging the potential for visits to any website. In this article, digital marketing concepts and the technological aspects that affect the indexing made by search engines will be explored. The case study presented intends to demonstrate, in a simplified way, the importance and applicability of these concepts and techniques, proposing a set of improvements that should be implemented to improve the positioning of the "Termas de Chaves" website in the search engine page results.